Impact of stent designs of second‐generation drug‐eluting stents on long‐term outcomes in coronary bifurcation lesions. Issue 3 (30th July 2020) - Jang, Woo Jin; Chun, Woo Jung; Park, Ik Hyun; Choi, Ki Hong; Song, Young Bin; Koo, Bon‐Kwon; Doh, Joon‐Hyung; Hong, Soon‐Jun; Nam, Chang‐Wook; Gwon, Hyeon‐Cheol
Abstract: Objectives: We compared the long‐term clinical outcomes of four different types of second‐generation drug‐eluting stents (DESs) in coronary bifurcation lesions. Background: Clinical outcomes of different designs of second‐generation DESs are not well known in bifurcation lesions. Methods: Patients who underwent percutaneous coronary intervention with second‐generation DESs for coronary bifurcation lesion were enrolled from 21 centers in South Korea. A total of 2, 526 patients was evaluated and divided into four treatment groups according to DES type: bioabsorbable polymer biolimus‐eluting stent (BP‐BES group, n  = 514), platinum chromium everolimus‐eluting stent (PtCr‐EES group, n  = 473), cobalt nickel zotarolimus‐eluting stent (CoNi‐ZES group, n  = 736), or cobalt chromium everolimus‐eluting stent (CoCr‐EES group, n  = 803). Primary outcome was target lesion failure (TLF, defined as a composite of cardiac death, target vessel myocardial infarction, or target lesion revascularization). Inverse probability of treatment weighting (IPTW) was performed to reduce selection bias and potential confounding factors. Results: For 5 years of follow‐up, the rates of TLF among the four DES groups were not significantly different (6.2% for BP‐BES group, 8.2% for PtCr‐EES group, 6.5% for CoNi‐ZES group, and 8.6% for CoCr‐EES group, p  = .434). The results were consistent after IPTW adjustment (6.8, 8.4, 6.0, and 7.5%, respectively, p  = .554). In subgroup analysis, the similarity of long‐term outcomes among the four different types of second‐generation DES was consistent across subgroups regardless of side branch treatment ( p for interaction = .691). Conclusion: There seems to be no significant difference in long‐term clinical outcomes among patients who received different types of second‐generation DES for coronary bifurcation lesion.